Effects of mixed H(2)O-CH(3)CN and H(2)O-Hconme(2) solvents on the rate of cleavage of N-Benzylphthalamic Acid - Ariffin, Azhar; Khan, M.N.; Cheong, M.Y. (2008)
The values of pseudo first-order rate constants, k(1), for the O-cyclization and k(3) for N-cyclization of N-benzylphthalamic acid 1, obtained at 0.02M HCl and 35 degrees C, show a respective nonlinear increase from 17.6 x 10(-6) to 29.7 x 10(-6) s(-1) and decrease from 12.5 x 10(-7) to 3.75 x 10(-7) s(-1) with increase in the CH(3)CN content from 2 to 60% v/v in mixed aqueous solvent. Increase in the CH3CN content from 60 to 90% v/v decreases k(1) from 29.7 x 10(-6) to 24.4 x 10(-6) s(-1) and increases k(3) from 3.75 x 10(-7) to 14.7 x 10(-7) s(-1). The respective values of k(1) and k(3) decrease nonlinearly from 16.0 x 10(-6) to 3.0 x 10(-6) s(-1), and 14.0 x 10(-7) to similar to 4.0 x 10(-7) s(-1) with increase in the content of N,N-dimethyl-formamide (HCONMe(2)) from 2 to 80% v/v in mixed aqueous solvents. These results indicate rather mild rate-retarding effects of mixed H(2)O-CH(3)CN and H(2)O-HCONMe(2) solvents on the rates of the intramolecular reactions.